2016
DOI: 10.1002/ppul.23484
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of clinical swallowing evaluation for diagnosis of dysphagia in children with laryngomalacia or glossoptosis

Abstract: Dysphagia was highly prevalent in this sample. The sensitivity of clinical evaluation to detect laryngeal penetration and tracheal aspiration was low, as the majority of aspiration events were silent. The videofluoroscopic study is important in order to determine a safest method to feed the patient. Pediatr Pulmonol. 2017;52:41-47. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…Although the CFE does not involve radiation risk, it can only identify signs and symptoms during feeding. This is not ideal because more than 80% of pediatric aspiration is silent and therefore occurs without overt clinical signs 11, 2022 . Choosing the most sensitive test is critical because inadequately treated aspiration can lead to a variety of poor outcomes including pulmonary injury, failure to thrive and oral aversion 1, 2325 .…”
mentioning
confidence: 99%
“…Although the CFE does not involve radiation risk, it can only identify signs and symptoms during feeding. This is not ideal because more than 80% of pediatric aspiration is silent and therefore occurs without overt clinical signs 11, 2022 . Choosing the most sensitive test is critical because inadequately treated aspiration can lead to a variety of poor outcomes including pulmonary injury, failure to thrive and oral aversion 1, 2325 .…”
mentioning
confidence: 99%
“…Determining the true prevalence of dysphagia in children with laryngomalacia is difficult due to the low sensitivity (<50%) of the bedside swallow evaluation in identifying dysphagia in this population due to high rates of silent aspiration. 3 Hence, many children with laryngomalacia likely go undiagnosed. In our study, 57% of the children with laryngomalacia who were tested with an MBSS showed evidence of aspiration or laryngeal penetration.…”
Section: Discussionmentioning
confidence: 99%
“…We feel it is imperative to emphasize that the co-occurrence of downstream consequences with an anatomic concern is the key in decision-making, as many children have anatomic variants that do not cause functional issues. Anatomic targets for surgical intervention by the otolaryngologist may include ankyloglossia, adenotonsillar hypertrophy, laryngeal cleft, laryngomalacia, vocal fold movement impairment, and cricopharyngeal achalasia [4,22,[30][31][32][33][34].…”
Section: Surgical and Medical Managementmentioning
confidence: 99%